User Interface And User Experience Design Mathematics Learning Applications Flat Sided Space Building Materials For Junior High School - Elvara Purwati; Ahmad Anis Abdullah (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2025)
The low ability to solve mathematical problems in the flat sided geometric material is one of the reasons for the birth of various application-based learning media. The progress of the development of learning media is unfortunately not matched by analysis of the needs, suitability and comfort of users so that many learning media do not last long. Learning media is needed that can provide comfort, convenience and prioritize user needs, so an application-based learning application is designed for class VIII flat sided building materials by taking into accountuser interface anduser experience aims to present application-based learning media that provide comfort and suitability to users as assessed by material experts and media experts. Research using the type method Research and Development (R&D) scope of research without testing with the ADDIE development model which has a development procedure analysis, design, development and evaluation. The validity of the product is assessed through the validation instrument of material experts and media experts which are then processed using a formulaindex Aiken's v.The results of the research areprototype the application of mathematics learning media for class VIII flat sided geometric material which is validated with an average product validity value of 0.822 in the very valid category according to the material expert validator and 0.921 in the very valid category according to media experts.